ANALISIS TENTANG PROFIL GURU GEOGRAFI SMA DI KOTA PADANG PROVINSI SUMATERA BARAT - Ely Putri; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine and analyze the teacher profile of geography subjects in Padang City High School. The things meant are 1) the teacher's general identity, 2) self-development, 3) scientific publications and 4) innovative work. Type of quantitative descriptive research. The population is all geography teachers in Padang City and the sample is taken as a whole (total sampling), with a total of 68 people. Sources of data in the form of primary data and secondary data. Data collection techniques with 1) observation, 2) questionnaire 3) documentation. Data were analyzed using percentage techniques. Based on the results of this study it can be concluded 1) The general identity condition of geography teachers in Padang City High School consisting of ranks / groups is mostly IVA (56.52%), the last level of education is the majority of S1 (85.29%), tertiary universities from the majority of UNP ( 70.59%), the majority of teaching time is in the range of 31-35 years (29.42%), the majority employment status of civil servants (63.24%), the majority certification year is 2008 (31.42%). 2) Teacher self-development consisting of post-certification education with a percentage (8.57%), teachers who attended training during 2014 - 2019 with a percentage (30.88%), seminar activities as resource persons with a percentage (2.94%) , workshop activities with a percentage (2.94%). 3) Teacher scientific publications based on the results of research reports in education (2.94%), based on scientific writing (1.47%), and based on textbook publications (1.47%). 4) The innovative work of the teacher has a percentage that is, based on learning media, arts and methods (0%). So the quality of geography teachers in Padang City is still low as seen from the small number of teachers involved in self-development activities, scientific publications and very few teachers who have innovative work. Efforts in overcoming this problem are teachers taking part in training related to scientific publications and innovative works and the government is providing more training related to scientific publications and innovative works in order to improve the professionalism of geography teachers in Padang.